Rheumatoid Arthritis Is Associated With Increased Aortic Pulse-Wave Velocity, Which Is Reduced by Anti–Tumor Necrosis Factor-α Therapy - Kaisa Mäki-Petäjä; Frances Hall; A. D. Booth; Sharon Wallace; Yasmin Yasmin; P.W.P. Bearcroft; Srinivasan Harish; Anita Furlong; Carmel M. McEniery; John C. Brown; Ian B. Wilkinson (2006)
Background— Rheumatoid arthritis (RA) is associated with increased cardiovascular risk, which is not explained by traditional cardiovascular risk factors but may be due in part to increased aortic stiffness, an independent predictor of cardiovascular mortality. In the present study, our aim was to establish whether aortic stiffness is increased in RA and to investigate the relationship between inflammation and aortic stiffness. In addition, we tested the hypothesis that aortic stiffness could be reduced with anti–tumor necrosis factor-α (TNF-α) therapy. Methods and Results— Aortic pulse-wave velocity (PWV), augmentation index, and blood pressure were measured in 77 patients with RA and in 142 healthy individuals. Both acute and chronic inflammatory measures and disease activity were determined. The effect of anti-TNF-α therapy on PWV and endothelial function was measured in 9 RA patients at 0, 4, and 12 weeks. Median (interquartile range) aortic PWV was significantly higher in subjects with RA than in control subjects (8.35 [7.14 to 10.24] versus 7.52 [6.56 to 9.18] m/s, respectively; P =0.005). In multiple regression analyses, aortic PWV correlated independently with age, mean arterial pressure, and log-transformed C-reactive protein ( R 2 =0.701; P <0.0001). Aortic PWV was reduced significantly by anti-TNF-α therapy (8.82±2.04 versus 7.94±1.86 versus 7.68±1.56 m/s at weeks 0, 4, and 12, respectively; P <0.001); concomitantly, endothelial function improved. Conclusions— RA is associated with increased aortic stiffness, which correlates with current but not historical measures of inflammation, suggesting that increased aortic stiffness may be reversible. Indeed, anti-TNF-α therapy reduced aortic stiffness to a level comparable to that of healthy individuals. Therefore, effective control of inflammation may be of benefit in reducing cardiovascular risk in patients with RA.